Tren Nikah Muda dalam Islam: Peluang dan Hambatan di Era Modern - Rifky Nurhimawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Marriage in Islam is regarded as an act of worship that completes half of one's faith and serves as a means of preserving honor. In the context of marrying young, Islam encourages its followers not to delay marriage as long as there is readiness. However, in the modern era, marrying young faces complex challenges, especially when confronted with social realities, mental readiness, economic stability, education, spirituality, and health. The purpose of this research is to examine young marriage in Islam by highlighting its opportunities and obstacles amidst current social, economic, and cultural changes. To explore this, the author employs Karl Marx's conflict theory to analyze the opportunities and barriers arising from social dynamics. The method used is qualitative with an approach based on Islamic law and sociology. Data collection techniques include interviews and documentation. The research findings indicate that young marriage in Islam has the potential to serve as an alternative for creating a more Islamic societal structure, provided it is supported by policies that reduce social inequalities and strengthen education based on religious values. Karl Marx's conflict theory offers a critical perspective on the structural barriers that need to be addressed to achieve harmony between Islamic teachings and modern needs.